A systematic pattern generation system for manufacturing customized seamless multi-layer female soft body armour through dome-formation (moulding) techniques using 3D warp interlock fabrics. (October 2018) - Abtew, Mulat Alubel; Bruniaux, Pascal; Boussu, François; Loghin, Carmen; Cristian, Irina; Chen, Yan; Wang, Lichuan
Highlights: We propose a systematic pattern generation system for developing multi-layer female soft body armour panels. Parametrization process based on each layer thickness was used to generate different successive meshes. We have flattened the multi-layers mesh to acquire the different successive layers pattern. Manufacturing system for seamless female body armor with dome-formation process using 3D interlock fabrics was devised. Fitness and shapes of the moulded multi-layer panels were validated by draping on female physical mannequin. Abstract: Female participants in different perilous tasks including law enforcement offices have been considerably increased in the last few decades. However, they mostly wear men's body armour with smaller sizes which brings a negative upshot not only in ballistic protection performance, comfort, fitness but also in a psychological point of view. Hence, manufacturing female soft body armour based on their unique morphological differences for better ballistic protection without conceding fitness and comfort are in great demand. This research work presented a novel method using a systematic 3D design approach through parametrization process to generate block patterns for manufacturing successive layer in the panels. The deformable mesh on the 3D virtual adaptive female model was developed with grading values of zero. Parametrization process based on the thickness of each layer in the 3D design database was applied to generate the different successive meshes on the virtual mannequin with appropriate coordinates. Later, the multi-layers mesh developed on the virtual 3D female body has been flattened to acquire the different layer's pattern. Due to its excellent mouldability behaviour, 3D warp interlock fabrics made of high-performance fibre has been designed and developed to manufacture the seamless female body armour with a dome-formation process. The manufactured multi-layer panels were draped on the standard female physical mannequin for experimental validations. The result shows that the new 3D design approach and its manufacturing system was found easy and precise to generate the different multi-layer panels pattern for developing seamless female soft body armour.